Self‐Delivery Nanomedicine for Glutamine‐Starvation Enhanced Photodynamic Tumor Therapy. Issue 3 (11th November 2021) - Zhao, Lin‐Ping; Chen, Shao‐Yi; Zheng, Rong‐Rong; Kong, Ren‐Jiang; Rao, Xiao‐Na; Chen, A‐Li; Cheng, Hong; Zhang, Da‐Wei; Li, Shi‐Ying; Yu, Xi‐Yong
Abstract: Glutamine metabolism of tumor cells plays a crucial role in maintaining cell homeostasis and reducing oxidative damage. Herein, a valid strategy of inhibiting glutamine metabolism is proposed to amplify the oxidative damage of photodynamic therapy (PDT) to tumor cells. Specifically, the authors develop a drug co‐delivery system (designated as CeV) based on chlorine e6 (Ce6) and V9302 via the self‐assembly technology. In spite of the strong hydrophobicity of therapeutic agents, the assembled CeV holds a favorable dispersibility in water and an improved cellular uptake capability. Under light irradiation, the internalized CeV is capable of generating abundant reactive oxygen species (ROS) for PDT. More importantly, CeV can reduce the uptake of glutamine through V9302‐mediated alanine‐serine‐cysteine transporter of type‐2 (ASCT2) inhibition, leading to a reduced glutathione (GSH) production and an amplified oxidative stress. As a result, CeV has a robust PDT efficacy on tumor inhibition by the blockade of glutamine transport. Notably, CeV exhibits a superiority on tumor suppression over the single treatment as well as the combined administration of Ce6 and V9302, which indicates the advantage of CeV for synergistic treatment. It may serve as a novel nanoplatform for developing a drug co‐delivery system to improve PDT efficiency by inhibiting cell metabolism. Abstract : A drug co‐delivery system based on chlorine e6 (Ce6) and V9302 is prepared for glutamine‐starvation enhanced photodynamic therapy (PDT). V9302 could reduce the alanine‐serine‐cysteine transporter of type‐2 (ASCT2)‐depedent glutamine uptake by tumor cells, which would inhibit the biosynthesis of glutathione (GSH) and amplify the intracellular oxidative stress to improve the PDT efficiency of Ce6.